Gender-Based Assessment of Indigenous People towards Conservation, Management, and Perception in Taguibo Watershed, Butuan City, Philippines (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The Taguibo Watershed is a key biodiversity area in Caraga Region, providing a source of water to the entire city of Butuan. A gender-based analysis of Indigenous Peoples (IPs) in Taguibo watershed aims to determine the socioeconomic, conservation, environmental management practices and perception of male and female respondents. Following a mixed-method approach, the data were gathered through the use of structured survey questionnaires, key informant interviews, and validation through a focus group discussion. Data were analyzed using Spearman Correlation to determine the relationship. A total of 323 IP respondents, 113 (35%) were male and 210 (65%) were female. Most had low education and family income, high percentage of the occupation were housewives and farmers. Gender had a very highly significant (p.
Keywords: Conservation; Indigenous People; Perception; Taguibo Watershed